Prevalence of Hepatitis in Neonates and Children in Karachi (Medical Forum Monthly, 2024)
Inflammation of liver is known as “hepatitis” is commonly found in infant as neonatal hepatitis and in children as acute and chronic hepatitis. Neonatal hepatitis is a general term for inflammation of the liver that occurs shortly after birth in newborns (less than 3 months of age) for which a specific cause cannot be identified.Objectives: To provide an overview of current childhood statistics of hepatitis and jaundice to facilitate analysis of the impact of past research discoveries on outcome and provide essential information for prioritizing future research directions.Study Design: Experimental Study.Place and Duration of Study: This study was conducted at the Department of Histopathology, BMSI, JPMC, Karachi from May 2004 to March 2005.Materials and Methods: Slides / paraffin blocks of liver biopsies from patients under 15 years of age. The cases were of two categories i.e. retrospective and prospective. The distribution of 480 cases of hepatitis was according to Age and Sex. Total 200 (41.7%) cases were encountered in the youngest of 0-5 years age group, 180 (37.5%) cases in 6-10 years and only 100 (20.8%) cases in 11-15 age group.Results: The distribution of 24 cases of hepatitis was according to Age and Sex. Total 200 (41.7%) cases were encountered in the youngest of 0-5 years age group, 180 (37.5%) cases in 6-10 and only 100 (20.8%) cases in 11-15 age group.Conclusion: It is observed that the tendency of liver inflammation was decreased with increase in age and sexual differentiation showing male predominance with male to female ratio of 2:1. The inflammation of liver /hepatitis in young children, can be caused by infectious, metabolic, and genetic disorders. Physiological jaundice or neonatal hepatitis is mostly reported in male population than females, in children. In Karachi this is found that neonatal jaundice can be recovered with the growing age and it is found to be a common cause for enlargement of liver and associated liver diseases in infants and children that can lead to higher risks of acute or chronic liver diseases in adulthood.